1991
DOI: 10.1017/s0022215100116354
|View full text |Cite
|
Sign up to set email alerts
|

Tegmental dehiscence and brain herniation into the middle ear cleft

Abstract: The tegmen tympani may occasionally be breached by herniation of the temporal lobe with or without dural cover. The clinical presentation may be obvious with CSF otorrhoea but less so with apparent middle ear effusion, CSF rhinnorrhoea, conductive hearing loss, recurrrent meningitis or intracranial sepsis. Diagnosis requires suspicion of the condition, which may be aided by radiological imaging. Surgical repair is to be recommended: various techniques are available but bone enveloped by fascia placed by subtem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Despite various names according to the content of the herniated tissue (e.g., meningocele versus meningoencephalocele), the term meningoencephalocele may be used broadly in reference to the temporal bone [1]. Meningoencephaloceles can be classified into cranial and basal varieties; cranial meningoencephaloceles typically involve the occipital and frontonasal regions, while lateral temporal lobe meningoencephaloceles and midline temporal lobe meningoencephaloceles present as masses in the sphenoid sinus [3][4][5][6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite various names according to the content of the herniated tissue (e.g., meningocele versus meningoencephalocele), the term meningoencephalocele may be used broadly in reference to the temporal bone [1]. Meningoencephaloceles can be classified into cranial and basal varieties; cranial meningoencephaloceles typically involve the occipital and frontonasal regions, while lateral temporal lobe meningoencephaloceles and midline temporal lobe meningoencephaloceles present as masses in the sphenoid sinus [3][4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…Meningoencephaloceles in the temporal bone originate from defects in the bony floor of the lateral skull base, i.e., in the upper surface of the temporal bone, and can lead to cerebrospinal fluid (CSF) leaks or meningitis [1]. Trauma, surgery, and malignancy most commonly produce these defects, but the spontaneous development of these complications without identifiable causes is less common [2].…”
Section: Introductionmentioning
confidence: 99%
“…Diagnosis of TTD is crucial for preventing potential life-threatening central nervous system (CNS) infection and permanent neurological defect [2,3] . Associated neurological complications such as meningitis, encephalitis, or otogenic cerebral abscess may occur due to the formation of a pathological pathway between the subarachnoid space and middle ear cavity or direct exposure of dura or cerebral tissue [3] .…”
Section: Discussionmentioning
confidence: 99%
“…This may have been due to the meningocele forcing the malleus towards the lateral side and causing anterolateral displacement of the chorda tympanic nerve. Golding-Wood et al [2] have suggested that tegmental dehiscence may contribute to CHL through herniation of the temporal lobe, reducing ossicular mobility or disrupting the chain. CHL due to TTD and brain herniation without otitis media is uncommon; therefore, TTD should be included in the differentiated diagnosis of air-bone gap hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of an obvious ear infection, clinical suspicion of otogenic origin rests on little evidence [1]. Temporal bone imaging then becomes essential for diagnosis and treat ment planning.…”
Section: Introductionmentioning
confidence: 99%